Mortality-lowering effect of systemic corticosteroid therapy in severe tetanus - (:unkn) unknown (My University, 1988)
In a double-blind therapeutic trial, 32 patients suffering from severe tetanus were given prednisolone and 31 a placebo in addition to standard treatment. Mortality was lower in the prednisolone-treated group (31%) than in the placebo-treated group (55%). The women had more severe symptoms and a higher mortality than the men. The results suggest that the addition of a corticosteroid to standard treatment will lower mortality in tetanus, although meticulous nursing care is still the most important factor in treatment.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Adolescent; Male; Double-Blind Method; Adrenal Cortex Hormones; Prednisolone; Randomized Controlled Trials as Topic; Tetanus; Tetanus Antitoxin